1996
DOI: 10.1136/ard.55.9.627
|View full text |Cite
|
Sign up to set email alerts
|

Restrictions of T cell receptor beta chain repertoire in the peripheral blood of patients with systemic lupus erythematosus.

Abstract: Objective-To investigate whether oligoclonal T cell populations occur in peripheral blood lymphocytes from patients with systemic lupus erythematosus (SLE). Methods-RNA was extracted from the lymphocytes isolated from whole peripheral blood of five female patients filfilling ARA criteria for SLE and two healthy female controls, and synthesised into cDNA. CDR3 length spectratyping was performed using a polymerase chain reaction (PCR) run to saturation followed by a primer extension with a radioactively labelled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
1
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 31 publications
4
29
1
1
Order By: Relevance
“…Mackus et al reported that, in CLL, the absolute number of CD8 ϩ T cells is often increased, and much of this can be attributed to the increased frequency of CTL specific for persistent viruses, such as CMV (34). In contrast, many studies in other settings suggest that skewed repertoires represent deficits in T cells that correlate with other measures of T cell dysfunction (35,36). Correction of repertoire skewing in other settings such as HIV is associated with improved clinical outcome (16).…”
Section: Discussionmentioning
confidence: 90%
“…Mackus et al reported that, in CLL, the absolute number of CD8 ϩ T cells is often increased, and much of this can be attributed to the increased frequency of CTL specific for persistent viruses, such as CMV (34). In contrast, many studies in other settings suggest that skewed repertoires represent deficits in T cells that correlate with other measures of T cell dysfunction (35,36). Correction of repertoire skewing in other settings such as HIV is associated with improved clinical outcome (16).…”
Section: Discussionmentioning
confidence: 90%
“…For all of these reasons, true clonality in an autoimmune disease is not expected. Indeed, oligoclonality has been reported in studies of experimental autoimmunity in animals [17][18][19] as well as in human rheumatoid arthritis, [22][23][24] systemic lupus erythematosus, 43,44 and IgA nephropathy. 45 Clonal dominance also occurs in viral infection [46][47][48] and in response to tumors and during graft-versus-host disease.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 The skewing of CDR3 length in SLE reported by Kalden's group correlated positively with disease activity and these ®ndings have been extended in this issue.…”
Section: T Cells In Systemic Lupus Erythematosusmentioning
confidence: 57%